Upregulation of miRNA-301a-3p promotes tumor progression in gastric cancer by suppressing NKRF and activating NF-κB signaling - Xu, Xiaodong (Int J Oncol, 2020)
MicroRNA-301a (miRNA/miR-301a) and nuclear factor (NF)-κB signaling play important roles in tumor invasion, migration and progression. However, the role of miRNA-301a-3p in human gastric cancer (GC), and specifically in the activation of NF-κB signaling, remains unclear. The aim of the present study was to investigate miRNA-301a-3p expression in GC progression and the molecular mechanisms as regards the regulation of NF-κB signaling. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to detect miRNA-301a-3p expression in GC and paired normal tissues. The association between the expression of miRNA-301a-3p and patient pathological parameters and the prognosis of GC was statistically analyzed using an in situ hybridization (ISH) assay. An MTS assay and a Transwell assay were performed to evaluate the effects of miRNA-301a-3p on the proliferation, invasion and migration of GC cells. RT-qPCR and western blot analysis were used to analyze the association between miRNA-301a-3p and nuclear factor-κB repressing factor (NKRF) expression and the corresponding downstream NF-κB signaling molecules. A luciferase assay was used to verify the target effect of miRNA-301a-3p and NKRF. It was found that miRNA-301a-3p expression was significantly higher in 30 cases of primary GC compared with matched normal tissues. Additionally, the ISH assay indicated that the high expression of miRNA-301a-3p in GC was associated with tumor invasion depth, lymph node metastasis, lymph node invasion and tumor metastasis stage. Patients whose tumors had a higher miRNA-301a-3p expression level exhibited a poorer prognosis. The in vitro assay indicated that miRNA-301a-3p affected the proliferative and invasive ability of GC cells by targeting the expression of NKRF, which then affected NF-κB signaling. Therefore, it was hypothesize that miRNA-301a-3p promotes GC progression and affects the prognosis of patients with GC by targeting NKRF, which in turn, directly influences NF-κB activation.